PERAN TINDAK TUTUR KESANTUNAN BERBAHASA SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN METODE DISKUSI DI KELAS XI SMAN 1 BANTAENG - Nurfaizah Nurfaizah; Muliadi Muliadi; Andi Puspitasari (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This study aims to: 1) describe the form of interaction of politeness speech acts in learning Indonesian using the discussion method in class XI IPA 2 at SMAN 1 Bantaeng and 2) describe the role of politeness speech acts in learning Indonesian using the discussion method in class XI IPA 2 in SMAN 1 Bantaeng. This research was conducted in class XI IPA 2 SMAN 1 Bantaeng with a total of 32 students consisting of 18 female students and 14 male students. Data collection techniques used interviews, recording and recording techniques which were analyzed using a qualitative descriptive research type. Using the discussion method in classroom learning with the results of the research showing that the student discussion method is more active and increases politeness in speaking. It can be seen that the results of the data on compliance with the maxims of tact show that there are 21 utterances that are in accordance with the principles of politeness maxims. Each utterance with its respective maxims has the role of speech act such as locutionary, illocutionary and perlocutionary. Researchers found that there were 34 speeches to be analyzed in accordance with the adherence to the principle of politeness.